M41 Recurrent Tuberculosis And Its Risk Factors In The Uk's Largest Tb Centre. (10th November 2014) - Avery, K; Ghani, R; Buckley, J; John, L; Davidson, RN
Abstract : Objective: To describe tuberculosis (TB) relapse/recurrence in patients treated at the UK's largest TB centre and identify characteristic which predicted recurrence. Design: Retrospective observational cohort study. Methods: All patients treated at our centre between 1st Jan 2002–31st Dec 2013 were identified from the local TB register. We excluded patients who died due to TB or whose outcome was unknown. Details of patients with more than one notification episode of TB were obtained from patient records. Results: In total, 3534 patients were treated for TB during the 12-yr period. After exclusions, 3515 patients were included in the study. Of these, 42 patients had two notifications of TB; none were treated more than twice. Of these 42, we considered 14 to be true relapses/recurrences. 28 patients were considered on review not to have had a true relapse/recurrence: of these, 11 had their first treatment episode at a different centre; 9 were re-starts of treatment because of non-adherence during the first TB episode; 2 had intracranial tuberculomas diagnosed within 12 months of initial episode; 6 were errors in notification. Of 14 patients considered to be true relapses/recurrence, 6 were microbiologically confirmed on relapse/recurrence and a further 8 were re-treated on clinical grounds. None exhibited drug resistance and 2 were HIV positive. The 14 true relapse/recurrence patients had mean age = 42 yrs (range 18–83 yrs) and 6 were males. The sites of relapse were: pulmonary in 6 cases, 3 patients had intracranial tuberculomas, 2 patients had bony TB, 3 patients had TB lymphadenitis. The mean time to relapse/recurrence was 41 months (range 2–96 mo). All 14 patients responded favourably to re-treatment. The true relapse rate of TB treated at the centre was 0.4%. The age, gender and ethnicity of the relapse cases were similar to the overall TB case-mix. Conclusions: Our true relapse/recurrence rate of TB is very low, and had no obvious risk factors. We cannot determine retrospectively whether these were recurrence or reinfection, but strain typing (DNA fingerprinting) could differentiate these.